2017
DOI: 10.37358/rc.17.8.5749
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Carbonyls Levels in Indoor Air in two Offices -Green and Old Building

Abstract: The concentrations of 17 carbonyl compounds were investigated in indoor air of two offices - one located in a green building and the other in an old building, both from Bucharest. Indoor air samples were collected during normal activities of the working staff on passive samplers. Two analytical techniques were used: Ion Chromatography for carboxylic acids and High Performance Liquid Chromatography for aldehydes and ketones. A questionnaire was administrated in order to collect information about buildings chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…This shows that parabens can be accumulated in sludge depending to chain length of alkyl derivate [1,6]. The profile of sludge composition is similar with that one reported in some US WWTPs in which MPB was detected in the highest concentration range (24.3-68.8ng/g), EPB has the second concentration levels (1.6-12ng/g), PPB presented concentrations ranging from 0.36-4.64ng/g [16,22].…”
Section: Methods Validationsupporting
confidence: 84%
“…This shows that parabens can be accumulated in sludge depending to chain length of alkyl derivate [1,6]. The profile of sludge composition is similar with that one reported in some US WWTPs in which MPB was detected in the highest concentration range (24.3-68.8ng/g), EPB has the second concentration levels (1.6-12ng/g), PPB presented concentrations ranging from 0.36-4.64ng/g [16,22].…”
Section: Methods Validationsupporting
confidence: 84%
“…We have seen an increased interest in indoor air quality, over the last few years, other than workplace atmospheres; this is due to: 1) awareness of the effects of building sealing measures and the excessive use of cleaning, maintenance and ambient products that have led, among other things, to an increase in concentrations and a greater diversification of chemical, physical or biological pollutants in the air with effect on the human health [1][2][3][4][5][6][7][8][9] and 2) the growth of indoors time spent; studies conducted in recent years it have shown that we spend 80-90% of the total time indoors. Generally, air quality is appreciated by reference to the limit values set by the World Health Organization (WHO) or other national/international regulations for each parameter.…”
mentioning
confidence: 99%